Immunolocalization of leptin and leptin receptor in colorectal mucosa of ulcerative colitis, Crohn’s disease and control subjects with no inflammatory bowel disease - Merigo, Flavia; Brandolese, Alessandro; Facchin, Sonia; Boschi, Federico; Di Chio, Marzia; Savarino, Edoardo; D’Incà, Renata; Sturniolo, Giacomo Carlo; Sbarbati, Andrea (Cell and tissue research, 2021)
The expression of leptin and leptin receptor (Ob-R) has been partially elucidated in colon of patients with inflammatory bowel diseases (IBDs), even though leptin is involved in angiogenesis and inflammation. We previously reported overexpression of GLUT5 fructose transporter, in aberrant clusters of lymphatic vessels in lamina propria of IBD and controls. Here, we examine leptin and Ob-R expression in the same biopsies. Specimens were obtained from patients with ulcerative colitis (UC), Crohn’s disease (CD) and controls who underwent screening for colorectal cancer, follow-up after polypectomy or with a history of lower gastrointestinal symptoms. Immunohistochemistry revealed leptin in apical and basolateral membranes of short epithelial portions, Ob-R on the apical pole of epithelial cells. Leptin and Ob-R were also identified in structures and cells scattered in the lamina propria . In UC, a significant correlation between leptin and Ob-R in the lamina propria was found in all inflamed samples, beyond non-inflamed samples of the proximal tract, while in CD, it was found in inflamed distal samples. Most of the leptin and Ob-R positive areas in the lamina propria were also GLUT5 immunoreactive in inflamed and non-inflamed mucosa. A significant correlation of leptin or Ob-R expression with GLUT5 was observed in the inflamed distal samples from UC. Our findings suggest that there are different sites of leptin and Ob-R expression in large intestine and those in lamina propria do not reflect the status of mucosal inflammation. The co-localization of leptin and/or Ob-R with GLUT5 may indicate concomitance effects in colorectal lamina propria areas.